Reactivity of transition-metal alloys to oxygen and sulfur - Tiwari, Rajarshi; Sanvito, Stefano (My University, 2021)
Oxidation and tarnishing are the two most common initial steps in the corrosive process of metals at ambient conditions. These are always initiated with O and S binding to a metallic surface, so that one can use the binding energy as a rough proxy for the metal reactivity. With this in mind, we present a systematic study of the binding energy of O and S across the entire transition metals’ composition space, namely, we explore the binding energy of 88 single-phase transition metals and of 646 transition-metal binary alloys. The analysis is performed by defining a suitable descriptor for the binding energy. This is here obtained by fitting several schemes, based on the original Newns-Anderson model, against density functional theory data for the 4d transition-metal series. Such descriptor is then applied to a vast database of electronic structures of transition-metal alloys, for which we are able to predict the range of binding energies across both the compositional and the structural spaces. Finally, we extend our analysis to ternary transition-metal alloys and identify the most resilient compounds to O and S binding.
PUBLISHED
Keywords: High-throughput calculations; Data mining; Band structure methods; Adsorption; Alloys; Physical Systems; Local density of states; Density of states; Composition; Chemical bonding; Nanoscience & Materials; Corrosion; Metals/Alloys; Physics; REACTIVITY